2020
DOI: 10.1002/ijgo.13490
|View full text |Cite
|
Sign up to set email alerts
|

Can in vitro maturation overcome cycles with repeated oocyte maturation arrest? A classification system for maturation arrest and a cohort study

Abstract: Objective To investigate the role of gonadotropin‐stimulated and human chorionic gonadotropin (hCG) ‐primed in vitro oocyte maturation (IVM) in cases of repeated in vitro fertilization (IVF) failure due to various forms of oocyte maturation arrest (OMA). Methods Retrospective cohort study. Results In all, 63 women with IVF failure due to OMA were evaluated in this study. According to the Hatirnaz & Dahan classification, 11 (17.5%) women were OMA type 1, 22 (34.9%) were OMA type 2, 0 were OMA type 3, 11 (17.5%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Oocyte maturation failure was defined as bad egg syndrome and its subtypes were mentioned in a previous study ( 5 ), which focused on oocytes instead of patients. An Hatirnaz and Dahan classification standard has been proposed for patients, which, however, merely applied to patients in whom all oocytes were immature ( 17 ). Considering that patients often obtained both mature and immature oocytes, even after modified ovarian stimulation in subsequent IVF cycles, and there were no appropriate classification criteria for them, we proposed a modified classification standard based on the existing one to classify patients with different OMA phenotype.…”
Section: Methodsmentioning
confidence: 99%
“…Oocyte maturation failure was defined as bad egg syndrome and its subtypes were mentioned in a previous study ( 5 ), which focused on oocytes instead of patients. An Hatirnaz and Dahan classification standard has been proposed for patients, which, however, merely applied to patients in whom all oocytes were immature ( 17 ). Considering that patients often obtained both mature and immature oocytes, even after modified ovarian stimulation in subsequent IVF cycles, and there were no appropriate classification criteria for them, we proposed a modified classification standard based on the existing one to classify patients with different OMA phenotype.…”
Section: Methodsmentioning
confidence: 99%
“…The Hatirnaz and Dahan classification systemin 2019 and the Beall et al in 2011 classification also both excluded patients with the diagnosis of EFS, premature ovarian failure (POI) and resistant ovary syndrome (ROS). Hatirnaz et al reported on a large number of OMA cases treated by FSH and hCG primed IVM cycles; however, no pregnancies were reported [ 6 ]. In the Hatirnaz and Dahan classification system, GV arrest was defined as Type I, MI arrest was defined as Type II, MII arrest was defined as Type III, GV-MI arrest was defined as Type IV and mixed arrest (GV, MI and MII) was defined as Type V [ 6 ].…”
Section: Nomenclature Of the Oocyte Maturation Abnormalitiesmentioning
confidence: 99%
“…Hatirnaz et al reported on a large number of OMA cases treated by FSH and hCG primed IVM cycles; however, no pregnancies were reported [ 6 ]. In the Hatirnaz and Dahan classification system, GV arrest was defined as Type I, MI arrest was defined as Type II, MII arrest was defined as Type III, GV-MI arrest was defined as Type IV and mixed arrest (GV, MI and MII) was defined as Type V [ 6 ].…”
Section: Nomenclature Of the Oocyte Maturation Abnormalitiesmentioning
confidence: 99%
See 2 more Smart Citations